The History of the New World : Benzoni's Historia del Mondo Nuovo - Benzoni, Girolamo, 1519-approximately 1570 (Book collections on Project MUSE., 2017)
"An abridged, annotated translation of Girolamo Benzoni's 1572 History of the New World, which describes firsthand encounters between Europeans and Native Americans, New World geography, and indigenous flora and fauna"--Provided by publisher